2018
DOI: 10.1007/s13224-018-1149-x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Blood Loss During Abdominal Hysterectomy with Intravenous Versus Topical Tranexamic Acid: A Double-Blind Randomized Controlled Trial

Abstract: Objectives To assess the effect of intravenous versus topical tranexamic acid in reducing intraoperative and postoperative blood loss in women with abdominal hysterectomy. Materials and MethodsThe study was a randomized double-blind placebo-controlled trial, carried out in a tertiary university hospital in Egypt, from November 2015 to October 2017. A total of 129 women undergoing abdominal hysterectomy for benign etiology were randomly assigned to three groups: Group I [43 patients received 110 ml normal salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…Many surgeons follow the practice based on their early training, rather than on the basis of scientific evidence [2]. Proponents believe that postoperative CSD reduces ecchymosis [3] and avoids hematoma formation, which impair wound healing by increasing wound tension and decreasing surrounding tissue blood perfusion [4]. In addition, a hematoma also may lead to superficial and deep-seated infection secondary to bacterial colonization [5].…”
Section: Introductionmentioning
confidence: 99%
“…Many surgeons follow the practice based on their early training, rather than on the basis of scientific evidence [2]. Proponents believe that postoperative CSD reduces ecchymosis [3] and avoids hematoma formation, which impair wound healing by increasing wound tension and decreasing surrounding tissue blood perfusion [4]. In addition, a hematoma also may lead to superficial and deep-seated infection secondary to bacterial colonization [5].…”
Section: Introductionmentioning
confidence: 99%
“…This is in comparison to the Cochrane Review of Surgical Approach to Hysterectomy for benign disease, which reported the median range of estimated blood loss for abdominal hysterectomies to be 238 to 650 mL. Similarly, recently published randomized trials including patients undergoing abdominal hysterectomy for uterine myomas estimated the blood loss to be 466 § 205 mL and the median to be 480 mL (350 −700 mL) [189,190].…”
Section: Intraoperative Blood Lossmentioning
confidence: 72%
“…The threshold used by the study investigators for the need for perioperative blood transfusion differed across the 15 studies. Two trials 56 , 60 relied on clinicians’ subjective decision, whereas seven 51 , 57–59 , 64–66 did not describe a protocol for triggering transfusions, and only six 50 , 52 , 53 , 55 , 61 , 63 relied on a fall in haemoglobin levels or clinically significant hypotensive episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Only five studies 50 , 52 , 57 , 59 , 67 considered mortality as an outcome. The duration of follow-up in these studies ranged from the hospital admission to 1 year.…”
Section: Meta-analysismentioning
confidence: 99%